ISO 14001 and beyond : environmental management systems in the real world - Sheldon, Christopher. (Greenleaf, 1997)
On September 1st 1996, ISO 14001 was published, worldwide. Written over five years in consultation with international industrial experts, non-governmental organisations and regulators, this environmental management systems standard will help organisations manage their impacts on the environment, no matter what their size, nature or location. The implications for the future are enormous. But what does the standard mean in the real world? What changes do managers have to make to accommodate its principles? What decisions need to be faced and when? Is it really going to make a difference or is it just another case of global greenwash? Will it be another missed opportunity for you, your organisation, or your market?At the start of what promises to be a worldwide explosion of interest in standardised EMSs, ISO 14001 and Beyond looks at their creation, their use, and their limitations, attempting to discover the essential truth about this important management tool.